2019
DOI: 10.1590/fst.18518
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and centesimal contents, antioxidant activity and antimicrobial action of phenolic compounds from Eugenia Brasiliensis Lam. Pulp

Abstract: Phenolic compounds (PC) have presented antioxidant potential as well as antimicrobial action against several bacteria. This study aimed to extract PC from grumixama (Eugenia brasiliensis Lam.) pulp using solid phase extraction (SPE), then quantify the PC by Folin-Ciocalteu assay, and to evaluate the antioxidant activity (AA) from PC by DPPH, ABTS and FRAP methods as well as its antimicrobial activity by plate diffusion assay (PDA) and Minimal Onhibitory Concentration (MOC) assays. Additionally, the centesimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…The assay was performed in triplicate. Antimicrobial activity was determined by following the formula below [ 58 ]:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay was performed in triplicate. Antimicrobial activity was determined by following the formula below [ 58 ]:…”
Section: Methodsmentioning
confidence: 99%
“…Sodium benzoate and potassium sorbate (dissolved in 20 mM sodium acetate buffer, pH 4) were used at the concentrations of 0.05%, 0.1%, 0.2% ( w / v ) and 0.01%, 0.05%, 0.1% ( w / v ), respectively (FDA-approved values). The antifungal activity was determined as described previously in the agar well diffusion method [ 57 , 58 ] at 30 °C after 48 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the grumixama fruit from Goiás has a higher citric acid content (1.16 g/100g fresh weight) and lower pH (3.39) than those of the fruit from Rio de Janeiro (0.29 g/100g fresh weight; 4.34, respectively) (AGUIAR et al, 2016). Soluble solid content of grumixama from Goiás (2.85 °Brix) was higher than those of the fruits from São Paulo (1.35 °Brix) and Santa Catarina (1.35 °Brix) (TEIXEIRA et al, 2015), but lower than that of grumixama from Ouro Preto (5.00 °Brix) (ZOLA et al, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Grumixama from Goiás has a carbohydrate content and energy value comparable to those of the fruits from São Paulo, Santa Catarina (TEIXEIRA et al, 2015) and Ouro Preto (ZOLA et al, 2019). However, it contains the lowest moisture concentration, which could be explained by the lack of precipitation in the dry season, which typically ranges from May to October in the Cerrado region.…”
Section: ------------------------------------------------------------mentioning
confidence: 97%